3D Analysis of the Forced Vibration of a Prestressed Rectangular Composite Plate With Two Neighboring Cylindrical Cavities - Akbarov, S. D.; Yahnioglu, N.; Yesil, U. Babuscu (TECH SCIENCE PRESS, 2012)
This paper presents an analysis of the forced vibration of an initially stressed rectangular composite plate containing two neighboring cylindrical cavities. The initial stresses are caused by stretching or compressing of the plate with uniformly distributed normal static forces acting on the two opposite end-planes which are parallel to the central axes of the aforementioned cylindrical cavities. The influence of the initial stresses on the stress concentration around the cavities caused by the additional uniformly distributed time harmonic forces acting on the upper face plane of the plate are given. The considered problem is formulated within the framework of the Three-Dimensional Linearized Theory of Elastic Waves in Initially Stressed Bodies. For the solution to this problem 3D FEM is employed. The numerical results on the influence of the initial stresses on the stress concentration around the cavities, as well as on the fundamental frequencies of the plate are presented and discussed.
Keywords: Initial stress; forced vibration; cylindrical cavity; 3D FEM; rectangular plate; composite; STRESS-CONCENTRATION; CIRCULAR HOLE; Computer Science; Materials Science